2016
DOI: 10.3732/apps.1500114
|View full text |Cite
|
Sign up to set email alerts
|

An ecological approach to measuring the evolutionary consequences of gene flow from crops to wild or weedy relatives

Abstract: Premise of the study:Agricultural practices routinely create opportunities for crops to hybridize with wild relatives, leading to crop gene introgression into wild genomes. Conservationists typically worry this introgression could lead to genetic homogenization of wild populations, over and above the central concern of transgene escape. Alternatively, viewing introgression as analogous to species invasion, we suggest that increased genetic diversity may likewise be an undesirable outcome.Methods:Here, we compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 50 publications
(57 reference statements)
3
14
0
Order By: Relevance
“…If Malaysian weeds are, in fact, a crucible where crop and wild alleles can recombine, the weeds could also potentially serve as a bridge for the introduction of crop alleles into wild populations (Snow et al 2010; Campbell et al 2016) or vice versa (Félix et al 2014). Of these two gene flow possibilities, wild-to-crop gene flow may be the less serious problem.…”
Section: Discussionmentioning
confidence: 99%
“…If Malaysian weeds are, in fact, a crucible where crop and wild alleles can recombine, the weeds could also potentially serve as a bridge for the introduction of crop alleles into wild populations (Snow et al 2010; Campbell et al 2016) or vice versa (Félix et al 2014). Of these two gene flow possibilities, wild-to-crop gene flow may be the less serious problem.…”
Section: Discussionmentioning
confidence: 99%
“…The introgression of new haplotypes or alleles between populations may lead to the homogenization of the populations' gene pool. A rare allele can be replaced by a common one from a different area (Olden et al 2004;Campbell et al 2016), and the loss of genetic variability of locally adapted populations can be disadvantageous to species in the long term, changing for instance the capacity to expand its distribution or increase vulnerability to the invasion of competitors (Olden et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We found the flowering stage class to have significantly higher levels of genetic variation when information theory-based calculations were employed whereas traditional population genetic measures demonstrated no detectable differences. The finding that Shannon-Wiener based-measures are more likely to detect differences among means has recently been noted with regard to crop-wild gene flow literature [3435] and reviewed in Sherwin et al [36]. Other plant studies of genetic variation in different plant stage classes have demonstrated mixed results with some studies finding no evidence for differences among stage classes (e.g., in another Trillium species; [46]) to those demonstrating significant differences (e.g., bamboo saplings had higher levels of genetic diversity than seedlings; [47]).…”
Section: Discussionmentioning
confidence: 99%
“…In GenAlEx v. 6.5 [33], we calculated Nei's unbiased gene diversity corrected for sample size (uHe) for all groupings. Recent work in the crop-wild gene flow literature (e.g., [3435]) and more broadly in population genetics [36], has demonstrated that information theory-based measures (i.e., Shannon-Weiner) may be more sensitive to detecting genetic diversity differences among groups than traditional population genetic measures. We therefore compared these measures (uHe vs. uS-W) in our data set here.…”
Section: Methodsmentioning
confidence: 99%